2019
DOI: 10.1186/s12906-019-2736-9
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of monotropein, astragalin, and spiraeoside on oxidative stress, endoplasmic reticulum stress, and mitochondrial signaling pathway in varicocelized rats

Abstract: Background: Monotropein, astragalin, and spiraeoside (MAS) are active compounds extracted from medicinal herbs; monotropein from Morinda officinalis How (Rubiaceae), astragalin (kaempferol 3-O-glucoside) from Cuscuta chinensis Lamark (Convolvulaceae) and spiraeoside from the outer scales of Allium cepa L. (Liliceae) in a ratio of 6.69:0.41:3.61. Monotropein, astragalin, and spiraeoside are well-known antioxidants, anti-inflammatory, and antinociceptive agents. The current investigation aims to study the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
5
44
0
Order By: Relevance
“…Previous studies have demonstrated that Mtp exerts antiapoptotic and anti-inflammatory effects in osteoarthritis chondrocytes (21,24,25). nevertheless, the potential functions of Mtp in the progression of cVd are not completely understood.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated that Mtp exerts antiapoptotic and anti-inflammatory effects in osteoarthritis chondrocytes (21,24,25). nevertheless, the potential functions of Mtp in the progression of cVd are not completely understood.…”
Section: Discussionmentioning
confidence: 97%
“…Stress-induced testicular dysfunction and corresponding pathological features have been well documented in rats [26]. MOTILIPERM has been used as an antioxidant to reduce lipid peroxidation, scavenge free radicles, and prevent germ cell apoptosis in varicoceles and drug-induced testicular toxicity [19,20,[23][24][25]. The present study reported for the first time the effect of MOTILIPERM on reproductive parameters in immobilization stress-induced male infertility in adult SD rats.…”
Section: Discussionmentioning
confidence: 62%
“…The components of MOTILIPERM, Morinda officinalis How (Rubiaceae) root, Cuscuta chinensis Lamark (Convolvulaceae) seed, and Allium cepa L. (Liliaceae) outer scales, reportedly possess a wide spectrum of pharmacological activities, such as antioxidant, antinociceptive, and anti-inflammatory activities [8,17,18]. Due to the synergistic effects of polyherbal formulations, MOTILIPERM has a vast advantage over single herbal formulations [19,20]. The marker compounds in MOTILIPERM include monotropein, diacetyl asperulosidic acid, kaempferol 3-O-glucoside, quercetin 4 -O-glucoside, and quercetin [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations